1996
DOI: 10.1007/s002689900165
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Supplemental l‐Arginine in a Chemical‐Induced Model of Colorectal Cancer

Abstract: L-Arginine inhibits the development of spontaneous, transplantable solid tumors and chemically induced mammary tumors. The aim of the present study was to investigate the effect of l-arginine on chemically induced colorectal cancer in male Wistar rats. Colorectal cancer was induced in all animals by weekly subcutaneous injections of the colonic procarcinogen 1,2-dimethylhydrazine (DMH) at a dosage of 20 mg/kg body weight. Arginine was given in a 1% solution of drinking water. Group I was the DMH control; group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 19 publications
1
28
0
Order By: Relevance
“…The location, area (size), macroscopic type, tumor architecture, number of blood vessels, and inflammatory infiltrate of all tumors were described by a single pathologist (D.O'R.). The volume of tumors was calculated as described [31]. The area was calculated after the tumor was divided into two-one portion for cell proliferation studies and one portion for morphological assessment.…”
Section: Animals and Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The location, area (size), macroscopic type, tumor architecture, number of blood vessels, and inflammatory infiltrate of all tumors were described by a single pathologist (D.O'R.). The volume of tumors was calculated as described [31]. The area was calculated after the tumor was divided into two-one portion for cell proliferation studies and one portion for morphological assessment.…”
Section: Animals and Treatmentsmentioning
confidence: 99%
“…L-arginine, a semiessential amino acid, reduces tumor production in some tumor models including chemically induced and transplantable solid tumors [27][28][29][30][31]. Arginine's effect on host-tumor interaction, which has been correlated with immune enhancement, appears to be optimal at supplemental concentrations between 0.5 and 1% [30,32].…”
Section: Introductionmentioning
confidence: 99%
“…Besides a genetic pre-disposition, diet also determines the risk for colon cancer and predominantly diets rich in fruits and vegetables diminish the risk of the disease [3]. 1,2-Dimethylhydrazine-induced model is utilized frequently, as it is similar to histopathological and molecular characteristics of human colon cancer model [4]. 1,2-Dimethylhydrazine is metabolized in liver to form azoxymethane and methylazoxymethanol later on transported to colon via bile or blood to generate its ultimate carcinogenic metabolite, diazonium ion which elicits an oxidative stress by methylating biomolecules of colonic epithelial cells and leads to promutagenic events as a result of inflammation and tumours in colon [5].…”
mentioning
confidence: 99%
“…Animal studies showed that experimental colonic tumors induced by DMH were of epithelial origin with a similar histology, morphology and anatomy to human colonic neoplasms [14] . This procarcinogen could thus provide an adequate model for studying colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%